2009
DOI: 10.1007/978-1-60327-414-2_5
|View full text |Cite
|
Sign up to set email alerts
|

Fish’n ChIPs: Chromatin Immunoprecipitation in the Zebrafish Embryo

Abstract: Chromatin immunoprecipitation (ChIP) is arguably the assay of choice to determine the genomic localization of DNA- or chromatin-binding proteins, including post-translationally modified histones, in cells. The increasing importance of the zebrafish, Danio rerio, as a model organism in functional genomics has recently sparked investigations of ChIP-based genome-scale mapping of modified histones on promoters, and studies on the role of specific transcription factors in developmental processes. ChIP assays used … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
58
0

Year Published

2010
2010
2022
2022

Publication Types

Select...
4
4

Relationship

1
7

Authors

Journals

citations
Cited by 64 publications
(58 citation statements)
references
References 18 publications
0
58
0
Order By: Relevance
“…ChIP analysis was basically carried out as described previously (66,67) using specific antibodies: anti-monoMeK4H3 (ab8895; Abcam), anti-diMeK4H3 (UP07-030; Upstate), and anti-triMeK4H3 (ab8580; Abcam). Two hundred fifty embryos were used for each assay, and cells were sonicated by a Branson Sonifier 250.…”
Section: Methodsmentioning
confidence: 99%
“…ChIP analysis was basically carried out as described previously (66,67) using specific antibodies: anti-monoMeK4H3 (ab8895; Abcam), anti-diMeK4H3 (UP07-030; Upstate), and anti-triMeK4H3 (ab8580; Abcam). Two hundred fifty embryos were used for each assay, and cells were sonicated by a Branson Sonifier 250.…”
Section: Methodsmentioning
confidence: 99%
“…Embryos/larvae were processed for RNA extraction as described above or for ChIP using the MAGnify Chromatin Immunoprecipitation System (Life Technologies). Briefly, for each immunoprecipitation 200 embryos (30 hpf) or 80 larvae (72 hpf) were cross-linked with 1% formaldehyde for 8 min, and the chromatin was sheared by sonication to an average fragment size of 500-1,000 bp (77). Lysates were cleared by centrifugation and diluted 1:10 in the dilution buffer of the ChIP kit, and immunoprecipitation was performed with 2-4 μg of antibody.…”
Section: Microinjection Of Morpholino Nucleotides or Rna Into Zebrafimentioning
confidence: 99%
“…The antibodies used in this assay were anti-H3 (ab1791; Abcam), anti-H3K4me3 (ab1012; Abcam), anti-H3K9ac (06-942; Millipore), and control mouse and rabbit anti-IgG provided by the MAGnify kit. All these antibodies have been validated in zebrafish previously (77), and the epitopes that they recognize are identical in zebrafish and mammals.…”
Section: Microinjection Of Morpholino Nucleotides or Rna Into Zebrafimentioning
confidence: 99%
“…Aiming at understanding epigenetic states during zebrafish development, we recently optimized a ChIP assay for zebrafish embryos, resulting in minimal chromatin loss and epitope degradation (Lindeman et al, 2009). We applied this ChIP assay to determine histone PTM enrichment profiles on the promoters of a subset of developmentally-regulated genes in embryos at the mid-late blastula transition (referred to as MBT + ), i.e.…”
Section: Gene-specific Post-translational Histone Modifications In Emmentioning
confidence: 99%
“…Of note, these ChIP protocols relied on protease treatment of embryos to remove the chorion prior to isolating chromatin. By re-assessing each step of the ChIP assay, we recently reported that proteases are detrimental to ChIP efficiency in zebrafish embryos, and subsequently improved the procedure (Lindeman et al, 2009). …”
Section: Introductionmentioning
confidence: 99%